OFFSET GUIDE OF THE ZEISS-2000 TELESCOPE - Karpov, N. V.; Choliy, V. Ya. (Одеські астрономічні публікації, 2007)
We present offset guide of 2-m-Zeiss-RCC telescope of the Terskol observatory. The main goal of the device is to help in the observations of the faint or moving objects and made the process as much as possible automatic. The device is equiped with the optical system, CCD cameras and controller to connect the device to the computer. Hardware is controlled with the software written in our team. That software is working unger Windows operation system and is based upon the system level hooks which allow us to catch the messages from the mouse and keyboard and react accordingly. Second part of the software manages the messages sent to and received from the stepping motors microprocessor controller which are used to manipulate with the position of the optical system of the device. There are two different setup mode of the offset guide: guiding of the inmovable objects and guiding of the moving objects like comet or asteroid. The management of the optical subsystem and CCD cameras is doing in both cases by software only. First results of the observations with the new offset guide show us that the device is quite usefull in the automatization of the observation on 2-meter-RCC telescope.